The prevalence, radiographic appearance and gender predilection of bifid mandibular condyles in Punjabi population of North India: A retrospective study - Bhawandeep Kaur; Sarfaraz Padda (Wolters Kluwer Medknow Publications, 2017)
Aim: The aim of this study was to determine the prevalence and gender predilection of bifid mandibular condyle (BMC) in Indian population using extra oral radiographs. Material and Methods: Previous record of 800 patients was evaluated by the observers who had undergone extra oral radiography for any diagnostic or treatment purposes between years 2012 and 2014. Results: Out of 800 extra oral radiographs, bifid condyles were found in 28, giving an overall prevalence of 3.5%. Out of 28 bifid condyles, 20 were in females (2.5%) and eight were in males (1.7%). The prevalence of BMC was found to be more in females as compared to the males and this difference was statistically significant with P value equivalent to 0.001. Among 28 bifid condyles, 19 were unilateral (2.4%) and nine were bilateral 1.5%. Chi-square test shows non-significant P value. Conclusion: It is possible that BMC is a more frequent condition than is commonly perceived. However, because of the minimal symptoms associated with this condition, the authors believe that it will remain an incidental finding upon routine radiographic examination, rather than a clinical observation.